Kualitas Audit: Ditinjau dari Fee Audit, Risiko Audit dan Skeptisme Profesional Auditor sebagai Variabel Moderating - Pratiwi, Alma; Muslim, Muslim; Rahim, Syamsuri; Pelu, Muhammad Faisal AR (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
The purpose of this study was to determine the effect of audit fees and audit risk on audit quality with auditor professional skepticism as a moderating variable. This research was conducted at 8 public accounting firms in Makassar city with 40 respondents. The analytical method used is multiple regression analysis (Moderated Regression Analysis) which is used to measure the strength of the relationship between two or more variables. The results of this study found that the audit fee variable had a negative and not significant effect on audit quality. These results illustrate that the higher the audit fee received by the auditor, the audit quality will decrease. While audit risk is not a significant positive effect on audit quality. The results of this study illustrate that the higher the audit risk, the audit quality will decrease. The auditor's professional skepticism as a moderating variable is not able to strengthen the effect of audit fees on audit quality. Furthermore, auditor professional skepticism as a moderating variable is also unable to strengthen the effect of audit risk on audit quality